AB0184 Applying the conrew score to camera -trial ii data. (23rd January 2014) - Jurgens, M. S.; vd Goes, M. C.; Bakker, M. F.; Welsing, P. M.; Boers, M.; Bijlsma, J. W.; Lafeber, F. P.; Jacobs, J. W.
Abstract : Background: In the two-year Computer Assisted Management in Early Rheumatoid Arthritis-trial II (CAMERA-II)(1 ), patients with early rheumatoid arthritis were randomized to a methotrexate (MTX-) based tight control strategy with either additionally 10mg/d prednisone (MTX+pred) or placebo (MTX+plac) from start. Until the first sustained (≥3 months) period of remission, time (in months(SD)) was shorter in the MTX+pred group than in the MTX+plac group (6(5) vs.11(5) resp., p<0.001). In the MTX+pred group more patients achieved at least one period of sustained remission, although not significantly different (72% vs. 61%, p=0.09). There is a need for methods to describe both the duration of remission as well as the interruptions in this desired state, which are simple to use. The continuity rewarded ("ConRew") score was developed with this purpose.(2 ) Objectives: To apply the ConRew score algorithm on the CAMERA-II data to study the difference between the two strategy arms and to study if this is a more sensitive way of addressing differences in remission than a simple sum score of remission periods. Methods: All 236 patients of the CAMERA-II trial (MTX+pred n=117, MTX+plac n=119) were studied to calculate scores. Remission was defined as a swollen joint count of 0 (range 0-38 joints), and at least 2 of the following factors: tender joint count ≤3 (range 0-38 joints), VAS score ≤20mm and ESR ≤20mm/h. Remission was evaluated in one-month time periods. The ConRew method scores a point for each remission period of a predefined length, adding a point for every period that is continuous with the next period of remission (continuity rewarding)and for being in remission at the end of the observation period (maximum of 2 points per period). To compare the ConRew method, also a plain sum score was calculated by adding the number of remission periods of a predefined length. Results: The mean (SD) ConRew score differed statistically significantly between the two strategy arms in favour of the MTX+pred group: 22(16) vs.17(14), p=0.004. The mean (SD) plain sum score was in favour of the MTX+pred group, but did not differ significantly (13(8) vs. 11(7), p=0.051). Effect size of the difference between the strategy arms measured through ConRew was larger than the effect size measured through the sum score (Cohen's d = 0.374 vs. Cohen's d = 0.255). Conclusions: There is a significant difference in sustained remission between the two treatment arms, favouring MTX+pred. The ConRew score appeared to be a better alternative to the sustained remission variable in CAMERA-II. Although both the effect size values are in the small to medium range, the fact that the ConRew effect size is almost 1.5 times larger shows a more sensitive way of addressing sustained remission. References: Bakker MF et al. Low-dose prednisone inclusion in a Methotrexate-Based, Tight Control Strategy for Early Rheumatoid Arthritis. A Randomized Trial. Ann Intern Med 2012;156:329-39. Boers M et al. A new graph and scoring system simplified analysis of changing states: disease remissions in a rheumatoid arthritis clinical trial. J Clin Epidemiol 2010;63:633-7. Disclosure of Interest: None Declared